Pengaruh Kerja Sama Tim, Komunikasi, dan Komitmen terhadap Kinerja Karyawan di PDAM Tirta Deli - Lubis, Imam Khairum Miza; Rukmini; Sembiring, Zamaluddin; Wibowo, M. Rizaldy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine the effect of teamwork, communication and commitment on employee performance at PDAM Tirta Deli either partially or simultaneously. This type of research uses primary data and secondary data. While data collection techniques using observation, questionnaires and interviews. The sample of PDAM Tirta Deli employees is 43 employees. Data analysis techniques using multiple linear regression analysis, hypothesis testing (t test and F test), and the coefficient of determination. The results of this study prove that partially it is known that the t-count of Teamwork (X1) is 2,704 > 1,682, Communication (X2) is 2,309 > 1,682, and Commitment (X3) is 2,158 > 1,622, then H0 is rejected and Ha is accepted, which means it influences Employee performance, and simultaneously it is known that the F-count value is 20,706> F-table 2.85, so there is an influence of teamwork, communication and commitment to employee performance at PDAM Tirta Deli. Keywords: Teamwork, Communication, Commitment, Employee Performance